Climate – grazing interactions in Mongolian rangelands: Effects of grazing change along a large-scale environmental gradient - Ahlborn, Julian; von Wehrden, Henrik; Lang, Birgit; Römermann, Christine; Oyunbileg, Munkhzul; Oyuntsetseg, Batlai; Wesche, Karsten (Journal of arid environments, 2020)
There are still major gaps in our understanding of rangeland degradation. Assessing the interactions between climate and grazing effects could help to explain what unifies and separates rangelands, and may therefore promote a more sustainable management of livestock. We studied 15 local land-use transects along a 600 km long climatic gradient in Central Asia to test the hypothesis that grazing effects differ between relatively moist equilibrium (EQ) and dry non-equilibrium (NEQ) rangeland systems. We analysed plant community composition, species diversity and indicator species for different grazing intensities. We found pronounced differences in community composition along our climate gradient, revealed climate-related grazing effects on richness, responses of Simpson's diversity, and also found different grazing indicator species along the larger transect. We conclude that in NEQ rangelands, grazing effects are limited to sacrifice zones and environmental filtering dominates vegetation composition. With increasing precipitation, resource availability gains in importance leading to more complex communities dominated by grazing-tolerant species under EQ dynamics. Hints for xerophytization in the transition zone between EQ and NEQ highlight the vulnerability of rangelands that temporally shift from one state to the other. This calls for extra care in the management of livestock numbers in these transition areas. •In non-equilibrium systems, grazing effects occur only in sacrifice zones.•Community composition varies strongly between non-equilibrium sites.•Community composition is very similar between and within equilibrium sites.•Grazing impacts on species richness increase with precipitation.•Xerophytization occurs in the transition zone between both systems.